2018
DOI: 10.1002/bkcs.11588
|View full text |Cite
|
Sign up to set email alerts
|

Trigraphene and its Derivates: A Novel Carbon Allotrope

Abstract: A new family of all-carbon structures is proposed via substituting the sp 2 carbon atom in graphene and graphyne with carbon trigons. Owing to the existence of carbon trigons, these porous carbon allotropes are named as trigraphene and trigraphyne. The calculations of geometrical, vibrational, and energetic properties by density functional theory reveal that all these structures are metastable and dynamically stable. It is further disclosed from the electronic band structures that trigraphene and α-trigraphyne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…Trigraphene as well as a-trigraphyne possess metallic properties, while band g-trigraphyne are indirect band gap semiconductors. 46 In the present study, we propose a new carbon-based sheet, named twin a-trigraphyne. The structural, mechanical, electronic, and optical properties of twin a-trigraphyne are compared to those of a-trigraphyne.…”
Section: Marzieh Nadafanmentioning
confidence: 99%
See 1 more Smart Citation
“…Trigraphene as well as a-trigraphyne possess metallic properties, while band g-trigraphyne are indirect band gap semiconductors. 46 In the present study, we propose a new carbon-based sheet, named twin a-trigraphyne. The structural, mechanical, electronic, and optical properties of twin a-trigraphyne are compared to those of a-trigraphyne.…”
Section: Marzieh Nadafanmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45] Recently, by replacing carbon trigons instead of sp 2 carbon atoms in graphene and graphyne, new forms of 2D carbon allotropes named trigraphene and trigraphyne have been introduced. 46 It has been shown that these constructed sheets are energetically favorable and dynamically stable. Trigraphene as well as a-trigraphyne possess metallic properties, while band g-trigraphyne are indirect band gap semiconductors.…”
Section: Marzieh Nadafanmentioning
confidence: 99%
“…11 The angular strain due to the triangular rings reduces the cohesive energy (ΔE coh = +0.9 eV/atom with respect to graphene) and bestows anharmonicity in the system. 8 Typically a material expands on heating, and therefore, positive thermal expansion (PTE) is observed. Nevertheless, several new materials have been found which contract on heating, showing negative thermal expansion (NTE), like oxides, halides, and other minerals, framework materials bridged by ligands like CN − and SCN − .…”
mentioning
confidence: 99%
“…T-graphene (TG) and tri-graphene (TrG), having tetra-rings (4-membered rings) and tri-rings (3-membered rings/trigons), respectively, have generated significant interest. , Even in the absence of hexagonal symmetry, planar TG is metallic while buckled TG is proposed to have a graphene-like Dirac cone with linear E ( k ) vs k near the Fermi level. Kim et al showed that buckled TG spontaneously transforms to the planar form .…”
mentioning
confidence: 99%
See 1 more Smart Citation